Palliative Stenting With or Without Radiotherapy for Inoperable Esophageal Carcinoma - Yaldiera Utami; Achmad Fauzi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Aim: to evaluate the comparison of palliative treatment using esophageal stenting alone or in combination with radiotherapy.Method: Patient/problem, intervention, comparison, and outcome (PICO) system were used. We conduct a searching in PubMed site. The next process was selection by reading all articles (10 articles). There were 9 articles excluded from analysis. We finally choose one randomized trial study written by Javed A, Pal S, Dash NR, Ahuja V, Mohanti BK, Vishnubhatla S, et al goes to the critical appraisal step.Results: The result of this study showed that dysphagia scores improved significantly in both groups, in patients with inoperable esophageal cancer treated with esophageal stenting alone (group I) and a combination of esophageal stenting and radiotherapy (group II) following stent insertion. However, dysphagia relief was more sustained in Group II than in Group I (7 vs. 3 months, p = 0.002).Conclusion: In this evidence-based case report (EBCR), we reported a man who suffered from dysphagia caused by inoperable esophageal carcinoma. Based on the critical appraisal of the randomized trial collected previously from PubMed with specific criterias, we conclude that a combination of esophageal stent and radiotherapy effectively prolongs duration of dysphagia relief and improves the overall survival, without increasing the incidence of complications.